In vitro evaluation of temperature rise during different post space preparations - Gokturk, Hakan; Ozkocak, Ismail; Taskan, Mehmet Murat; Aytac, Fatma; Karaarslan, Emine Sirin (European Journal of Dentistry, 2015)
Objective: The aim of this study was to evaluate temperature alterations on the outer root surface during post space preparation with six different post drills by using an infrared thermometer. Materials and Methods: Sixty extracted single-rooted human mandibular incisor teeth were used. After root canal obturation, the specimens were divided into six groups (n = 10). During post space preparation, the temperature rises were measured in the middle third of the roots using a noncontact infrared thermometer with a sensitivity of 0.1°C. The temperature data were transferred from the thermometer to the computer and were observed graphically. Results: The maximum temperature rise was observed in Snowpost 2 (29.95 ± 10.2°C) (P < 0.001), but there were no significant differences among Snowpost 2 (29.95 ± 10.2°C), Snowpost 1 (24.6 ± 8.0°C), and Relyx 2 (17.68 ± 9.1°C) (P > 0.05). Conclusions: Although water coolant used, the critical temperature rise was observed on the outer root surface in all post drill systems.
Keywords: Endodontics; infrared thermometer; post space preparation; temperature increase; thermal analysis